2019
DOI: 10.4274/tjps.galenos.2018.90522
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy as a Complementary Medicine for Multiple Sclerosis

Abstract: Multipl skleroz (MS), dünya çapında yetişkinlerde en sık görülen nörolojik problemdir. MS hastalarının pek çok sorunla karşı karşıya kalmasına neden olan iki ana sorun bulunmaktadır. İlk sorun, MS'in kesin nedeninin henüz belirlenmemiş olmasıdır. Diğer problem ise bu hastalık için kesin bir tedavinin olmayışıdır. Bu nedenle, MS'li hastalar, bu hastalığın semptomlarını giderebilmek için tamamlayıcı ve alternatif tedavi arayışındadırlar. Aynı zamanda, tıbbi bitkilerin, MS'in farklı modellerde tedavisinde olası o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The second most cited benefit was for pain and disease management (38.5%). There is empirical support for the effectiveness of cannabis in combating chronic pain (Romero-Sandoval et al, 2018), pain associated with cancer (Bonini et al, 2018), pain associated with multiple sclerosis (Rabiei, 2019), and insomnia (Babson et al, 2017;Klumpers & Thacker, 2019). Recent research found support for the beneficial effects of cannabis on depression (Premoli et al, 2019;Silote et al, 2019), PTSD (Ney et al, 2019), and irritable bowels (Couch et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most cited benefit was for pain and disease management (38.5%). There is empirical support for the effectiveness of cannabis in combating chronic pain (Romero-Sandoval et al, 2018), pain associated with cancer (Bonini et al, 2018), pain associated with multiple sclerosis (Rabiei, 2019), and insomnia (Babson et al, 2017;Klumpers & Thacker, 2019). Recent research found support for the beneficial effects of cannabis on depression (Premoli et al, 2019;Silote et al, 2019), PTSD (Ney et al, 2019), and irritable bowels (Couch et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The use of cannabis to address pain, seizures, nausea, sleep disturbance, and loss of appetite has been the most conclusive. Analgesic effects (Bonini et al, 2018;Klumpers & Thacker, 2019;Rabiei, 2019;Romero-Sandoval et al, 2018;Wilkie et al, 2016), anticonvulsant effects (Bonini et al, 2018;Klumpers & Thacker, 2019;Premoli et al, 2019), and antiemetic effects (Bonini et al, 2018;Klumpers & Thacker, 2019;Premoli et al, 2019) have been documented. Circadian regulation effects have been found to be effective in addressing various types of sleep disturbance (Babson et al, 2017;Klumpers & Thacker, 2019).…”
Section: Cannabis and Healthmentioning
confidence: 99%
“…The sedative and antidepressant effects of phytotherapy, along with improvements in sleep quality, decreases in muscle rigidity, neuropathic pain, and the degree of pelvic organ dysfunction have drawn attention. 35 A positive therapeutic effect was also noted with the use of plant polyphenols, which include chrysin extracted from the plant Passiflora caerulea. Chrysin has antioxidant, anti-inflammatory and neuroprotective effects.…”
Section: Phytotherapymentioning
confidence: 99%
“…It causes significant multifocal demyelination in both gray and white matter, and axonal damage via an autoimmune mechanism directly linked to neuroinflammation [161]. The stimulation of the immune system is not completely understood [162], but it is believed that both genetic and environmental factors are the main triggers [12].…”
Section: Cannabinoids and Multiple Sclerosismentioning
confidence: 99%